Destilação atmosférica de biodieseis derivados do óleo da amêndoa da macaúba (Acrocomia aculeata) e do palmiste (Elaeis guineensis) para obtenção da Fração de Ésteres Leves para uso em misturas com o querosene de aviação - Harter, Luiz Vitor Leonardi (2019)
The production of methyl esters via transesterification reaction of triacylglycerides of macaúba and palm kernel oils, with subsequent atmospheric distillation and separation of six fractions of the produced biodiesel, corresponding to 60 % of its initial volume, is reported. The composition in esters of the produced biodiesel, its fractions and remaining residue of the distillation was determined by gas chromatography. This analytical procedure has allowed to monitor the content in esters for each distilled fraction. The fractions richer in C8:0, C10:0, C12:0, C14:0 is intended to be used as an aviation fuel, in blends with the Jet-A1 biokerosene. The residues from the distillation with higher molecular weights than those corresponding to esters C16:0, C18:0 and C18:1 are destined to other combustion engines as any conventional biodiesel. For the biodiesel obtained from the macaúba kernel, this distillation led to an enrichment from 45.86 % to up to 74.35 % in the C12:0 ester. For the palm kernel biodiesel, the corresponding enrichment was from 66.76 % up to 82.96 %. Through this simple distillation, it was thus possible to effectively enrich, in C8:0 to C14:0 esters, the initial crude biofuel, with an efficiency of 30 % for the macaúba and 11.5 % for the palmiste biodiesel. In the present study, the light distillate mixtures were prepared with Jet A-1 kerosene and characterized by parameters, specific mass, flash point, distillation range, moisture content, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) - freezing point and calorific value. These analyzes were performed as parameters to determine the best relationship between JET A-1 and light (distilled) biodiesel, based on the values indicated by the ANP for the verified characteristics. Mixtures equivalent to 5 %, 10 % and 20 % by volume of distilled short chain esters of macauba or palm kernel, with Jet A-1 showed results within the limits recommended by resolutions ANP 37 and ASTM D1655, except the freezing point, being close to the 5 % mixture.